Traversing Central Prague from Jan Palach Square to Ukrainian Heroes’ Street: The Symbolic Function of Place Names in a Linguistic Landscape - Martina Ptáčníková (Folia Onomastica Croatica, 2022)
This paper investigates the phenomenon of renaming public spaces so common in urban history since the second half of the 19th century. The research focuses on instances of spontaneous renaming initiated by the general public rather than those brought about by the local self-government. A number of notable examples of Czech as well as Czechoslovak urbanonyms are provided, covering the period starting from the Second World War until the present. Special emphasis is put on the spontaneous origin of the urbanonym náměstí Jana Palacha (Jan Palach Square) commemorating the student who set himself on fire and burned himself to death in protest against the Soviet invasion of Czechoslovakia in 1968. The conclusion addresses, among other things, the topical issue of renaming a range of public spaces in response to the Russian military aggression against Ukraine. In Prague, Ukrajinských hrdinů (Ukrainian Heroes’ [Street]) and Skakunův most (Skakun Bridge) are among the commemorative place names to have appeared recently.